Isu Persaingan Industri Pelayanan Kesehatan Indonesia: Tantangan dan “Perisai” Pengawasan KPPU - Muhammad Alfarizi; Zela Zalika (Jurnal Persaingan Usaha, 2023)
The COVID-19 pandemic and the Epidemiological Transition are driving the pace of development of an increasingly advanced health system. The health service industry revolution has made all providers compete with each other to gain a competitive advantage amid Indonesia's potential health market. The insistence on oversight of competition in the health industry that is free from elements of the crime is fundamental to ensure that no party is disadvantaged in the healthcare industry environment. This study aims to analyze the phenomenon of competition in the health service industry, the clinic industry, hospitals, health insurance, clinical pharmacy, medical devices, and traditional medicine in Indonesia from the perspective of business competition law and review the role of the Business Competition Supervisory Commission (KPPU) in preventing monopolistic practices. And unfair business competition in the health services sub-sector. This study uses a PRISMA-based systematic literature review with 38 articles ready for analysis. The results showed that competitor in the healthcare industry was hidden but dangerous, namely cheating and hiding hands with patients, the health business mafia, and corporate monopoly, which occupied the highest health business rating. Apart from that, KPPU found a crucial role in the shield function of supervising competition in the health service industry, which is very intriguing and full of loopholes for law violations.